Identification of genetic heterogeneity in the Cryptosporidium parvum ribosomal repeat. - Carraway, M (1996)
Oocysts of the protozoan parasite Cryptosporidium parvum are found in most surface waters and can contaminate municipal water supplies, as demonstrated by recent outbreaks of cryptosporidiosis. A method capable of fingerprinting C. parvum isolates from the environment would facilitate the study of epidemiology and transmission cycles and aid in the implementation of preventive measures to reduce water contamination by oocytes. In this study, we report polymorphism in C. parvum isolates on the basis of analysis of random amplified polymorphic DNA and nucleotide sequences in a region of the 18S rRNA and the internal transcribed spacer 1. Isolate-specific primers for these two regions were designed, and PCR tests capable of discriminating between isolates were developed. In both PCR assays, the five C. parvum isolates analyzed segregated into two subgroups. One group consisted of isolates that originated directly from human patients, and the other group had various host origins and had been propagated in laboratory animals. These results demonstrate the feasibility of distinguishing C. parvum isolates by sequence-specific PCR tests.